Effect of brazing parameters on microstructure and mechanical properties of TMC/Si3N4 joint. Issue 1 (July 2021) - Shi, Kangqiao; Li, Min; Zhu, Dongdong; Dong, Duo; Xie, Lei; Zhang, Tong
Abstract: A multilayered filler made up of Cu foam and Ag-28Cu foils was used to successfully braze (TiB+Y2 O3 )/titanium matrix composites (TMC) and silicon nitride ceramics (Si3 N4 ). The microstructure of the TMC/Si3 N4 joints obtained at different brazing parameters was investigated. The results showed the interfacial structure of the joints is composed of TiCu, TiCu2, Ag (s, s), Cu (s, s), TiN and Ti5 Si3 phases. The growth equation of the TiN layer was established and its thickness was increased with respect to the brazing time and brazing temperature. Optimal shear strength of approximately 180 MPa was achieved when the joint was brazed for 10 min.